Two step synthesis of a non-symmetric acetylcholinesterase reactivator - Musílek, Kamil; Kuča, Kamil; Dohnal, Vlastimil; Jun, Daniel; Marek, Jan; Kolečkář, Vít (Molecules, 2007)
The newly developed and very promising acetylcholinesterase reactivator (E)-1-(2-hydroxyiminomethylpyridinium)-4-(4-hydroxyiminomethylpyridinium)-but-2-ene dibromide was prepared using two different pathways via a two-step synthesis involving the appropriate (E)-1-(4-bromobut-2-enyl)-2- or 4-hydroxyiminomethyl-pyridinium bromides. Afterwards, purities and yields of the desired product prepared by both routes were compared. Finally, its potency to reactivate several nerve agent-inhibited acetylcholinesterases was tested.
Keywords: Pyridinium Compounds; financování organizované; Financing, Organized; pyridinové sloučeniny; bromované uhlovodíky; Hydrocarbons, Brominated; reaktivátory cholinesterasy; Cholinesterase Reactivators